2022
DOI: 10.1007/s00477-022-02310-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal statistical analysis of PM1 and PM2.5 concentrations and their key influencing factors at Guayaquil city, Ecuador

Abstract: Guayaquil, Ecuador, is in a tropical area on the equatorial Pacific Ocean coast of South America. Since 2008 the city has been increasing its population, vehicle fleet and manufacturing industries. Within the city there are various industrial and urban land uses sharing the same space. With regard to air quality there is a lack of government information on it. Therefore, the research’s aim was to investigate the spatio-temporal characteristics of PM1 and PM2.5 concentrations and their main influencing factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…Contrasted results are also found for wind speed and PM 2.5 concentration. [36][37][38], concluding that the relation wind speed -PM 2.5 is nonlinear (polynomial) over time. A lower wind speed does not favor the pollutants dispersion, while a moderate increase in wind speed allows their dispersion.…”
Section: Atmospheric Conditionsmentioning
confidence: 94%
“…Contrasted results are also found for wind speed and PM 2.5 concentration. [36][37][38], concluding that the relation wind speed -PM 2.5 is nonlinear (polynomial) over time. A lower wind speed does not favor the pollutants dispersion, while a moderate increase in wind speed allows their dispersion.…”
Section: Atmospheric Conditionsmentioning
confidence: 94%
“…Ordinary linear regression (OLS) was used to determine the linear relationship between influencing factors and PM 2.5 . Due to the fact that simple OLS cannot accurately explore the relationship between various factors and PM 2.5 , scholars have started to use methods such as logistic regression [12] and multiple linear regression [13,14]. With the deepening of research, it has been found that the spatial distribution of various factors can also affect the concentration of PM 2.5 , so Geographically Weighted Regression (GWR) has been introduced.…”
Section: Introductionmentioning
confidence: 99%